Knowledge attitude and practice of haemovigilance among doctors in tertiary care hospital in Nagpur, Maharashtra, India - Date, Amit P.; Date, Anjali A.; Dashputra, Amruta V.; Borkar, Archana S. (International Journal of Basic & Clinical Pharmacology, 2016)
Background: Haemovigilance program of India was launched on December 2012 and is a comprehensive, and a well-structured approach to collect, collate, and analyse data to address the issues of adverse reactions associated with blood transfusion. The information thus collected would facilitate corrective and preventive actions to be taken to minimize the potential risk associated blood collection processing and transfusion to patients. Considering the deep concern over the under-reporting of transfusion reactions prevailing among the doctors, the present study was done to know the knowledge attitude and practice (KAP) of haemovigilance among doctors. Methods: The present study was a cross sectional questionnaire based study, which included doctors of a tertiary care hospital. The purpose of the questionnaire was to know awareness of doctors regarding haemovigilance programme of India. With this study we also tried to identify the factors responsible for underreporting of transfusion reactions and to find out the possible ways to improve reporting of transfusion reactions. Results: (38.88%) and (30%) of the responders were aware of the haemovigilance programme and transfusion reaction reporting centre respectively. Reporting of transfusion reaction was poor 22.22% among the respondents. According to respondents creating awareness about haemovigilance by conducting continuing medical education (CMEs), and training to healthcare professionals would lead to improvement in reporting of transfusion reactions. Complacency and ignorance were the main factors which discouraged transfusion reaction reporting by doctors. Conclusions: Increasing awareness of haemovigilance among doctors and training on reporting transfusion reactions would likely improve spontaneous reporting and help to strengthen the blood transfusion system.